Effect of toothpastes with different abrasives on eroded human enamel: an in situ/ex vivo study - Ferreira, Meire Coelho; Ramos-Jorge, Maria Letícia; Delbem, Alberto Carlos Botazzo [UNESP]; Vieira, Ricardo de Souza (My University, 2013)
The aim of the present study was to investigate the abrasive effect of CaCO3 and SiO2-based fluoride-free experimental toothpastes on eroded human permanent dental enamel and evaluate the effectiveness of waiting periods between acid exposure and tooth brushing. Twelve volunteers wore palatal appliances containing human enamel blocks for two periods of five days each. The appliances were immersed in a soft drink for five minutes four times a day (9:00 am, 11:00 am, 2:00 pm and 4:00 pm). On two occasions, two blocks were not submitted to additional treatment; two blocks were brushed (30 s) either with a CaCO3 or SiO2 toothpaste immediately after erosion and two blocks were brushed 1 h after erosion. Thus, the sample was divided into six groups: erosion alone (CaCO3 and SiO2 control); brushing with fluoride- free toothpaste (CaCO3 immediate and 1 h after erosion; SiO2 immediate and 1 h after erosion). Significant differences in wear depth were found between the enamel blocks in the CaCO3 immediate and 1 h after erosion groups and the blocks in the CaCO3 control group (p=0.001; p=0.022). No significant differences were found regarding the change in roughness and wear depth between blocks submitted to immediate abrasion and 1 h after erosion (CaCO3 and SiO2). The data revealed that surface roughness and wear depth is increased when erosion is combined with dental abrasion, regardless of the abrasive used. Waiting for 1 h to brush the eroded blocks offered no protective effect.
Keywords: Carbonated beverages; Dental enamel; Tooth abrasion; Tooth erosion; Toothpaste